ISOLASI SENYAWA AKTIF DARI BELALUQ LESOOQ (CLOTARIA PALLIDA AITON) TUMBUHAN OBAT ASLI KALIMANTAN TIMUR DAN KALIMANTAN UTARA SEBAGAI BAHAN KOSMETIK - Purba, Ritson; Tsunami, Anissa (PROSIDING SEMINAR KIMIA, 2024)
Isolation of active compounds from medicinal plants native to East and North Kalimantan, namely Belalauq Lesooq (Crotalaria pallida), was carried out to obtain isolates from this plant. This research aims to determine the anti-bacterial and antioxidant activity of the plant. Isolation is carried out by fractionation or isolation methods using a chromatography column with a solvent gradient system. Starting from n hexane followed by a more polar solvent. where the crude plant extract is directly fractionated using a solvent of the lowest polarity, namely n-hexane, followed by adding a more polar solvent. The extract previously used was an extract obtained from the extraction of dry powder from the young leaves of the Belalauq Lesooq (Crotalaria pallida) plant. Isolation was carried out on this plant with an isolation yield for Belalauq Lesooq (Crotalaria pallida) of 90.64%. The isolates that were tested for their antioxidant activity and anti-bacterial P. acne (anti-acne) were the best isolates (BS18). The BS18 isolate was obtained at 0.2310 grams. The antioxidant activity test was found to be 32.82 mg/L using the DPPH reduction method (IC50) with the antibacterial P. acne inhibitory power being 13.33 mm. Where BS18 is a pure isolate obtained from n-hexane: ethyl acetate 6:4 fractionation. Keywords: isolation, antioxidant, P.acne bacteria, cosmetics.